Screening and performance of L-14, a novel, highly efficient and low temperature-resistant cellulose-degrading strain - Zheng, Guoxiang; Lu, Zhaoxin; Li, Jian; Ai, Shuang (International Journal of Agricultural and Biological Engineering, 2020)
In view of the low bioconversion efficiency of agricultural biomass waste in low-temperature environments in winter, a low-temperature-resistant cellulose-degrading strain, L-14, was successfully screened by restrictive cultures from humus-rich soil in the Daqing Zhalong wetland region. According to morphological observations and 18S rDNA sequence analysis, the cellulose-degrading strain L-14 was identified as a Neurospora sp, belonging to fungus. Different parameters, such as temperature, initial pH, carbon, nitrogen and lecithin, were optimized using a single-factor experiment and a response surface methodology (RSM). When the temperature was 16°C, the optimal conditions for enzyme production were an initial pH 8.20, 10.45 g/L of bran, 5.28 g/L of yeast powder, and 4.25 g/L of lecithin. The carboxymethyl cellulase (CMCase) activity of strain L-14 was 63.598 IU/mL. Strain L-14 had a high level of cellulose degradation activity, excellent resistance to low temperatures and environmental adaptability, indicating its good application prospects in substrates pretreatment of biogas engineering. Keywords: low-temperature-resistant, Neurospora sp., 18S rDNA sequence, carboxymethyl cellulase, response surface methodology DOI: 10.25165/j.ijabe.20201301.5128 Citation: Zheng G X, Lu Z X, Li J, Ai S, Sun Y. Screening and performance of L-14, a novel, highly efficient and low temperature-resistant cellulose-degrading strain. Int J Agric & Biol Eng, 2020; 13(1): 247–254.